The effects of porcine somatotropin (pST) dosage and dietary lysine level on growth performance and carcass characteristics of finishing swine - B R Schricker; G R Stoner; R J Danler; R C Thaler; B P Kenny; S S Hurt; G E Fitzner; J Apple; K Warren; Robert D Goodband; Jim L Nelssen; Robert H Hines; et al. (Kansas Agricultural Experiment Station Research Reports, 1988)
One hundred and forty-four finishing pigs (initial weight 126 lb) were utilized to determine the effects of PST dosage (4 or 8 mg PST' head^-1day^-1 ) and dietary lysine level (.8, 1,0, 1.2, or 1.4%) on growth performance and carcass characteristics. Pigs were injected daily in the extensor muscle of the neck with either 4 or 8 mg PST and fed a pelleted corn-soybean meal-sesame meal diet containing .8% lysine. Additional lysine levels of 1.0, 1.2, and 1.4% were provided by L-lysine HCl. Control pigs (placebo injection) received the .8% lysine diet. All diets were formulated to contain at least 220% of NRC (1979) recommendations for other amino acids, vitamins and minerals. There were no PST x lysine interactions for any observed traits (P>,1 0), so only main effects are reported. Increasing level of dietary lysine resulted in linear improvements in average daily gain (ADG) and feed conversion (F/G) in PST treated pigs. Adjusted backfat thickness (ABF) was lowered (linear P.10) by increasing dietary lysine level and were also increased (linear P<.10) by PST dosage.; Swine Day, Manhattan, KS, November 17, 1988
Keywords: Swine day; 1988; Kansas Agricultural Experiment Station contribution; no. 88-149-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 556; Swine; Porcine somatotropin; Dosage; Lysine requirement; Growth performance; Carcass traits; Finishing pigs